HOW MUCH INFLUENCE LEADERSHIP MANAGERIAL COMPETENCE ON MADRASAH PERFORMANCE IN INDONESIA: A META-ANALYSIS AND SYSTEMATIC REVIEW APPROACH - Romli, Ombi; Tarihoran, Naf’an; Nugraha, Enung (International Journal of Multidisciplinary Research and Literature, 2025)
The success of school management, especially madrasah, cannot escape the important role of leadership, leaders who have good managerial skills are needed in advancing an educational institution so that the impact on the performance of an institution will be felt. through the systematic literature review and meta-analysis approach methods in this research process. The data collection process was conducted through a literature search. This study examined the effect of leadership managerial competence on madrasah performance in Indonesia. The study results show that there is a positive correlation between the managerial competence of school principals and the performance of education personnel. Effective madrasah leadership depends not only on strong managerial skills, but also includes supervision of learning and efforts to foster a positive school culture. Furthermore, research found that principals' managerial competence, along with school culture and teachers' work discipline, collectively contributed 91.22% to the variation in madrasah quality. In addition, principals' managerial competence and teacher professionalism jointly influenced teacher performance, explaining 51.8% of the observed variance. These findings confirm that leadership managerial competence plays an important role in improving the effective performance of education personnel, building a conducive school culture and improving the overall quality of education in madrasahs.